Small-Scale Fisheries and Sudden Disaster: Covid-19 Lockdown Impacts on Catch Composition and Livelihoods of Artisanal Fishers in Bangladesh: Catch and Livelihood Changes in Bangladesh’s SSF During COVID-19 - Rahman, Muhammad Mizanur; Akter, Morgina; Rahman, Md Shajjadur; Sultana, Nahid; Sultana, Tanjida; Sarker, Subrata (Journal of the Sylhet Agricultural University, 2025)
Globally, the COVID-19 pandemic disrupted systems related to food, transportation, and livelihood. The pandemic harmed small-scale fishermen (SSF). However, little is known about the COVID-19’s impact on artisanal fishing communities, particularly catch composition. Therefore, this study aimed to evaluate the effects of COVID-19 on artisanal fisheries in Bangladesh, employing Participatory Rural Appraisal (PRA) tools for data collection. Data were collected for 60 days (23 days of pre-lockdown and 37 days of lockdown) from seven landing sites in the southwest coastal zone of Bangladesh in 2020, focusing on fishing, catch, price, and livelihood status of fishermen. Observations revealed lower fishing pressure during lockdown, which benefited fishermen with a higher catch per unit effort (CPUE) than pre-lockdown. However, fishing became less profitable due to declining fish prices (4-83%) and increased transportation costs (average 30%) compared to the pre-lockdown times. These factors, combined with reduced fishing time (5 hours a day, 3 days a week) during the lockdown, significantly reduced the income of small-scale fishermen, compelling over 70% to seek high-interest loans from moneylenders, shopkeeper credits to cover living expenses. Around 22% of fishermen took loans with high interest from local lenders, which may affect them in the future, putting their next generations at risk of exploitation by the money lenders. Moreover, lockdown affected their livelihoods, with the highest impact on food (25%), followed by the economy (23%), health (20%), education (19%), and other social effects (13%). In this study, we propose a framework that can protect small-scale artisanal communities against future crises. J. Sylhet Agril. Univ. 12(1): 38-57, 2025